Isolation and characterization of an Escherichia coli mutant lacking cytochrome d terminal oxidase. - Green, G N (1983)
A screening procedure was devised which permitted the isolation of a cytochrome d-deficient mutant by its failure to oxidize the artificial electron donor N,N,N',N'-tetramethyl-p-phenylenediamine. Cytochrome a1 and probably cytochrome b558 were also missing in the mutant. Growth and oxygen uptake rates were similar for both parent and mutant strains. However, the strain lacking cytochrome d had an increased sensitivity to cyanide, indicating that cytochrome d confers some resistance to this respiratory inhibitor. The gene responsible for these phenotypes has been named cyd and maps between tolA and sucB.